SPATIAL ASSESSMENT OF ENVIRONMENTAL CONTAMINATION BY PESTICIDES IN THE MUNICIPALITY OF PETROLINA-PE – PART I - Barros, Marcos Antonio Sousa; de Albuquerque Junior, Eden Cavalcante (Seven Editora, 2025)
One way to assess the risk of environmental contamination from a pesticide is to consider its physical and chemical properties in terms of soil binding capacity, volatility, leachability, solubility, etc. The GOSS and GUS methods combine this information to create a contaminant profile, serving as a basis for assessing the potential for surface and groundwater contamination by a given pesticide. In this regard, several tools can be used, such as those that consider the combination of these and other models associated with Geographic Information Systems for mapping regions, where soil characteristics and available water resources provide a vulnerability profile for various locations, particularly agricultural producers. The sub-middle São Francisco region is one of Brazil’s main fruit producing and exporting hubs, specializing in grape and mango production. The agricultural system implemented in this region requires an assessment of its impacts on the environment, particularly on soil, water, and the atmosphere, through the physical, chemical, and biological characteristics of local natural resources. Controlling pesticide use in this region is a challenge for environmental oversight agencies. This study aims to assess the risk of environmental contamination in the agricultural regions of Petrolina, Pernambuco, based on information generated by a Geographic Information System (GIS). It considers physical aspects of the soil and water compartments, highlighting soil types, hydraulic conductivity potential, and slope, associated with the physicochemical properties of pesticides. These characteristics were found in samples from various crops collected in Petrolina during 2009, 2010, and 2011. Based on the proposed methods (GUS and GOSS), the study revealed high contamination potential for those pesticides that undergo leaching, particularly for azoxystrobin, boscalid, carbendazim, dimethomorph, fenarimol, methomyl, and myclobutanyl thiamethoxam. On the other hand, compounds such as Cyproconazole, Difenoconazole (1,2), Propargite, and Tebuconazole showed a high potential for contaminating surface water. Therefore, leachable pesticides should be avoided in soils with high hydraulic drainage, as well as in soils with relatively steep slopes. The combination of land vulnerability data with pesticide properties showed that it is possible to identify, preliminarily, contamination regions for different pesticides in the municipality of Petrolina. The combination of spatial data with chemical knowledge can point to more rational practices where crop/environment/pesticide should be considered as a whole with interrelationships. DOI: https://doi.org/10.56238/sevened2025.029-027